(untitled) (Confluências | Revista Interdisciplinar de Sociologia e Direito, 2013)
In the thesis Legal pluralism and incommensurability of values three general questions were posed as means of presenting explorative issue: 1) what is common in different faces of the concept of incommensurability of values (e.g. I. Berlin, J. Raz); 2) how the thesis about value pluralism could be transferred into legal sphere (particular examples) 3) why the concept of incommensurability of values could be fruitful for better understanding of some basic difficulties connected to pluralism of legal orders.